Portraits de métaphores - Anne-Sophie Collard (Communication)
This article proposes a reflection on the stakes involved in the use of metaphor to construct a hypermedia generated at the communicational level. It is inscribed in a cognitive approach to metaphorical understanding. The principal objective, beyond taking a « for or against » position towards the conceptual tool, is to propose three typologies of metaphor. The underlying hypothesis is that each category leads to particular effects on the user at the level of his/her understanding of the apparatus and at the level of his/her representation of the contents that this allows for.